Acetone gas sensor based on iron molybdate nanoparticles prepared by hydrothermal method with PVP as surfactant. (26th September 2018) - Zou, Shuang; Luo, Jing; Lin, Zhidong; Fu, Ping; Chen, Zhe
Abstract: The Fe2 (MoO4 )3 nanoparticles were prepared by hydrothermal method using polyvinyl pyrrolidone (PVP) as surfactant. The crystal phase, morphology and microstructure were characterized by x-ray diffraction, scanning electron microscopy. The results indicated the Fe2 (MoO4 )3 nanoparticles were composed of sphere-like monoclinic nanocrystals with average size of 50 nm. The sensor based on the Fe2 (MoO4 )3 nanoparticles exhibits good gas-sensing performances, especially to acetone. The response to acetone was significantly higher than that to other gases. The responses of the sensor were 2.45, 24.7, respectively, to 1 ppm and 100 ppm acetone at the optimal operating temperature of 340 °C. The Fe2 (MoO4 )3 nanoparticles can be potential material for high response and low concentration acetone selective sensor which can be applied in diabetes diagnosis.